THE LAW ON LAND ACQUISITION - Su, Tiang Joo, author 653472; Pang, Kong Leng, author 653473 (Ampang, Selangor Darul Ehsan : CLJ Publication, 2018)
The Federal Constitution provides that ‘no person shall be deprived of property save in accordance with law’; and ‘no law shall provide for the compulsory acquisition or use of property without adequate compensation’. It is therefore imperative for landowners to understand their rights to ensure that these rights are protected and adequately compensated in the event of compulsory acquisition. ‘The Law on Land Acquisition’ comprehensively sets out the underlying legal jurisprudence of compulsory land acquisition in Malaysia and the procedural pre-requisites based on the Land Acquisition Act 1960, including the recent amendments vide the Land Acquisition (Amendment) Act 2016. The book also highlights both reported and unreported case authorities up to 1 January 2018 that had seen law in this subject developed.